Produção recombinante e caracterização de uma legumaína de cana-de-açúcar - Buzolin, Ana Lígia (2014)
Cysteine proteases (CPs) are proteolytic enzymes which have a cysteine residue at its active site. Plant legumains are CPs known as vacuolar processing enzymes and they play key roles in seed maturation, germination, senescence, stress response, programmed cell death during development and defense against pathogens. Although there are many studies about plant legumains, most of them is related to legumain functions in seeds of dicotyledonous. To date, only one legumain from sugarcane has been described. In this study, it was performed the characterization of a new sugarcane legumain, named CaneLEG2. The recombinant CaneLEG2 was produced in the heterologous expression system Pichia pastoris and its kinetic characterization showed that it exhibits self-activation and activity under acidic pH, which are common features of plant legumains. This study also demonstrated that the sugarcane cystatin CaneCPI-3 has a strong inhibition over the CaneLEG2 activity, suggesting that this cystatin may participate of the regulation of endogenous cysteine proteases. The results obtained in this work will support the understanding of the functions of CaneLEG2 and CaneCPI-3 in sugarcane.